Electrochemical rebalancing process for vanadium flow batteries: Sizing and economic assessment. (February 2023) - Poli, Nicola; Trovò, Andrea; Fischer, Peter; Noack, Jens; Guarnieri, Massimo
Abstract: All-vanadium flow batteries (VFBs) may undergo electrolyte oxidation from atmospheric oxygen and/or hydrogen evolution because of operations at extreme states of charge. The consequent electrolyte imbalance reduces the battery capacity, impairing its potentially very long cycle life, but it cannot be recovered by a simple mixing operation. Among the different processes which have been proposed in the literature to rebalance the electrolyte and restore the VFB capacity, this paper consider the electrochemical method that uses an electrolysis reactor, consisting of stacks of several cells, to reduce V(V) in the positive electrolyte to the level of V(II) in the negative electrolyte. A techno-economical model is presented that includes the major parameters affecting the reactor and process performance, namely VFB rated energy and electrolyte imbalance rate, periodicity of the rebalancing process, rebalancing reactor current density, active area, cell number and rebalancing process duration. An analysis of the investment and operative expenditures is developed to analyze the effect of these parameters and their interplay on such costs and to identify the conditions to minimize such costs. The model indicates that relatively frequent rebalancing operations are economically preferable and consequently strategies of planned electrolyte rebalancing are proposed which allow to minimize the overall investment and operative costs deriving from mixing, rebalancing and VFB out of service. For the sake of example, numerical calculations are performed referring to a 500-kWh VFB, that is a quite common rating for VFBs, and they indicate that a cost reduction of almost 70 % is achieved if 10-hour processes are run four times per year instead of once a year. At this rebalancing frequency, the 500 kWh VFB needs a 9-kW reactor costing around €15.000. Graphical abstract: Unlabelled Image Highlights: A capacity rebalancing method for vanadium redox flow batteries is considered. The method uses an electrochemical cell for reducing V(V) in the catholyte. A techno-economical assessment for addressing its design is presented. The sizing and affordability of the method are discussed. Optimized dimensions and periodicity of operations are identified.